Implementation of Restorative Justice for Children at the Binjai Police - Yusuf Syahputra, Robby; Rahmayanti, Rahmayanti (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Law Number 11 of 2012 concerning the Juvenile Criminal Justice System shifts the paradigm of child handling from a retributive approach to a restorative one through a diversion mechanism. This study aims to analyze the effectiveness of the application of restorative justice in handling cases of child abuse in the jurisdiction of the Binjai Police. The method used is empirical juridical with a socio-legal research approach, including document studies, observations, and interviews with child perpetrators, victims, and investigators. Of the 36 cases of child abuse, 25 cases (69.4%) were resolved through diversion and 11 cases (30.6%) through the formal justice process. The research findings indicate that the application of restorative justice is effective in reducing the criminalization and stigmatization of children and is in line with the principle of the best interests of the child as specified in the SPPA Law. However, optimization of implementation needs to be done through strengthening human resources, improving coordination between stakeholders, and developing a periodic evaluation system. This research contributes to the development of a more humane and sustainable juvenile criminal justice policy.